Penyuluhan Bahaya dan Dampak Pernikahan Dini di Kelurahan Baru Tancung Kabupaten Wajo - Sulaeman; Firman; Mustari; Andi Muh. Nabil; Kasnadi, Andi Nabila; Muhammad Alif Chandra; Novia Surahma; Astuti Susanti (YP-SDI Lamaddukelleng, 2025)
This research is the result of community service activities conducted using counseling methods on the dangers and negative impacts of early marriage in Baru Tancung Village, Tanasitolo District, Wajo Regency. The counseling focused on delivering material on the impacts of early marriage on legal aspects, child protection aspects, health aspects, gender aspects, social aspects, and economic aspects. This counseling targeted an audience of mothers as parents who have the closest emotional connection to their children. This counseling succeeded in increasing mothers' understanding and awareness regarding the dangers and negative impacts of early marriage.